2021
DOI: 10.1039/d1ta04962c
|View full text |Cite
|
Sign up to set email alerts
|

Local electrocatalytic activity of PtRu supported on nitrogen-doped carbon nanotubes towards methanol oxidation by scanning electrochemical microscopy

Abstract: Nitrogen-doped carbon nanotubes (NCNTs) were synthesized by treating HNO3-oxidized carbon nanotubes (CNTs) in NH3 flow at different temperatures. PtRu nanoparticles were decorated over NCNTs. The PtRu catalysts were prepared by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…[28][29][30] They are sustainable and environmental friendly, contain large surface area, ordered structure, porosity, cost effectiveness, high conductivity, high abundance in earth and defects which provide enhanced activity. [29][30][31][32] By virtue of these fascinating properties, several carbon based catalysts with different morphology, porosity and heteroatom doping are being explored as an electrocatalyst for high yield production of H 2 O 2 . [9] In this regards, heteroatom doping into carbon framework is an efficient way to improve the activity by creation of several defects and thus tuning the electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] They are sustainable and environmental friendly, contain large surface area, ordered structure, porosity, cost effectiveness, high conductivity, high abundance in earth and defects which provide enhanced activity. [29][30][31][32] By virtue of these fascinating properties, several carbon based catalysts with different morphology, porosity and heteroatom doping are being explored as an electrocatalyst for high yield production of H 2 O 2 . [9] In this regards, heteroatom doping into carbon framework is an efficient way to improve the activity by creation of several defects and thus tuning the electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The B and N contents in the Rh/BNCNH framework are determined to be 1.5 and 2.7 at%, which are similar to those reported for B-doped or N-doped nanocarbon materials. 36,37 Fig. 4a reveals different B-related energy peaks centered at 191.8 and 192.8 eV, which are linked to the B-C3/B-N and B-C-O groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies demonstrated that the Pt-M nanoparticles with ordered structures showed promising improvement in the activity and stability of the catalyst. 25,26 For a bimetallic Pt-M alloy system (M = Ru, 27,28 Ni, 29 Cu, 30,31 Pb, 32 Co, 33,34 Sn, 35 etc. ), the addition of M can promote the adsorption and activation decomposition of water at a lower potential and provide adsorbed hydroxyl groups (OH ads ), which serve as oxidants to transform the toxic species (CO ads ) into CO 2 by oxidizing.…”
Section: Introductionmentioning
confidence: 99%